1984
DOI: 10.1177/009862838401100303
|View full text |Cite
|
Sign up to set email alerts
|

Staying with Initial Answers on Objective Tests: Is it a Myth?

Abstract: The common advice to not change answers appears to be a mistake, but before that is certain, additional information is needed.Since 1928, at least 33 studies have been published concerning a number of issues surrounding answer-changing behavior on objective tests. Although results in these studies have sometimes been at variance, the one consistent finding is that there is nothing inherently wrong with changing initial answers on objective tests. In fact, the evidence uniformly indicates that: (a) the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
77
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 32 publications
12
77
1
Order By: Relevance
“…The incidence of answer changing with the IF AT was higher than that reported previously (e.g. , Benjamin, Cavell, & Shallenberger, 1984), an inherent outcome of the answer-until-correct procedure. The correction of these initially inaccurate responses represents learning during the testing process and suggests that test takers refine decision making during testing.…”
Section: Discussioncontrasting
confidence: 72%
“…The incidence of answer changing with the IF AT was higher than that reported previously (e.g. , Benjamin, Cavell, & Shallenberger, 1984), an inherent outcome of the answer-until-correct procedure. The correction of these initially inaccurate responses represents learning during the testing process and suggests that test takers refine decision making during testing.…”
Section: Discussioncontrasting
confidence: 72%
“…In particular, there is research examining the impact of response changes on test performance (see Benjamin et al 1984;Mueller and Wasser 1977). For example, Geiger (1991) found that changing one's response led to score gains of 3 points on average and that students underestimate the benefit of changing responses.…”
Section: Test-taking Behaviorsmentioning
confidence: 99%
“…A hallmark of effective test-taking is the evaluation of one's answers and making changes to the answers when necessary (Benjamin et al 1984). However, under conditions of evaluation apprehension individuals tend to avoid risk, are overcautious, and exert unproductive effort (Eysenck et al 2007;Geen 1985;Maner et al 2007).…”
Section: Effect Of Stereotype Threat On Test-taking Behaviorsmentioning
confidence: 99%
“…C. Second-Guessing Second-guessing is an intensively studied topic in social and behavioral psychology. Research evidence showed that second-guessing was actually beneficial to people who changed their test answers (first instinct fallacy), because a complex thinking process was involved [4,5]. In sketch recognition tests, we want to know whether second-guessing had a positive or negative impact on participants' recognition rates.…”
Section: B Multi-matchmentioning
confidence: 99%
“…In cognitive psychology, multi-choice test has been used to study the uncertainties and indecisiveness in decision making strategies [4,5]. In sketch recognition tests, when given multiple sketches, volunteers showed their hesitation in the form of multi-match or second-guess.…”
Section: Introductionmentioning
confidence: 99%